In vitro response from cotyledon and hypocotyls explants in tomato by inducing 6-benzylaminopurine - Mohamed, Abd-Almajid Nasher; Ismail, Mohd Razi; Rahman, Mohamed Hasan (Academic Journals, 2010)
Differential response of tomato was evaluated by hypocotyls and cotyledon explants on 6-benzylaminopurine (BAP) containing MS media. Among the four levels (0, 1, 2 and 4 mg/l) of BAP employed in Murashige and Skoog (MS) media, 2.0 mg/l BAP was found superior in growth traits (number of shoots/explants and shoot length) and cultivars. No significant difference was noticed between cotyledon and hypocotyls explants on media having 2.0 mg/l BAP. In the same treatment, shoot length was significantly different between cotyledon and hypocotyls derived explants. No adventitious shoots was noted in the control and higher concentration of BAP containing media but the explants turned into callus on media having 4.0 mg/l BAP.